2007
DOI: 10.1155/2007/32528
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Vanadium Oxide Nanostructured Host Matrices for Lithium Ion Intercalation

Abstract: We report on unique high-volume low-dimensional V 2 O 5 -based turbostratic nanostructures, prepared using sol-gel synthetic methods from V 2 O 5 · nH 2 O xerogels. Electrochemical intercalation of Li + to form Li 0.65 V 2 O 5 resulted in a maximum measured charge capacity of 1225 mAh g −1 as the β-Li x V 2 O 5 phase. Conductivities of the order of 10 −3 S cm −1 were found on compressednanotube parallelepipedal samples, which exhibit an anisotropy factor of 70 at room temperature by preferential alignment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The association of nanoscale and atomic scale disorder appears to produce the best combination of increased specific capacity and better cyclability. Therefore, the unprecedented density of urchin’s nanotubes, could open new possibilities for making lithium nano-batteries [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of nanoscale and atomic scale disorder appears to produce the best combination of increased specific capacity and better cyclability. Therefore, the unprecedented density of urchin’s nanotubes, could open new possibilities for making lithium nano-batteries [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…[21] Urchin-like V 2 O 5 nanostructures have been obtained via such a glycothermal treatment in an ethanolic solution of vanadium tri-isopropoxide and alkyl amines. [22][23][24] Six-fold rotationally symmetric vanadium oxide nanostructures were obtained from V 2 O 5 xerogels assisted by dodecanethiol. [25] Vanadium oxides such as VO 2 petaloid clusters or VOOH hollow dandelions have also been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the SEM images of the samples revealed the formation of nanorod structures, similar to those reported earlier. [16][17][18][19] The present study examines the effect of meso-and macroporosity on the optical and electrochromic properties of sol-gel prepared vanadium oxide films. The formation of nanorods under different conditions is investigated in order to perfect a relatively facile method to synthesize vanadium oxide nanorod structures for EC applications.…”
mentioning
confidence: 99%
“…It should be noted that the V 2 O 5 nanostructures prepared by the above described methods were found to be redox active, undergoing a reversible reaction with lithium ions. The large lithium insertion capacity found for V 2 O 5 electrode in lithium-ion batteries was associated to the different topological intercalation sites provided by the nanotubular or nanorod host structures and the shorter diffusion paths involved 1,[16][17][18][19] It has been reported that templated sol-gel prepared WO 3 films yield, after the removal of the template, meso-(pores in the size range of 2 to 20 nm) or macro porous films with significantly enhanced electrochromic properties. [20][21][22][23][24][25][26][27][28][29][30][31] In order to create porosity in vanadium pentoxide xerogel prepared from a vanadium alkoxide, we have used polystyrene microspheres or a non-ionic polymer surfactant (Pluronic P-123) and heat-treated the dip-coated layers on ITO substrates at relatively high temperatures (400-500 • C).…”
mentioning
confidence: 99%